2012
DOI: 10.1055/s-0032-1312921
|View full text |Cite
|
Sign up to set email alerts
|

Raising Awareness about Chronic Intestinal Pseudo-Obstruction (CIPO): A Case Report Showing CIPO as Initial Manifestation of Atypical Seronegative Systemic Sclerosis

Abstract: Only few case studies address pseudo-obstruction, a disorder - which often frustrates clinicians and patients due to an unclear diagnosis and limited therapeutic options. Thus, the aim of this paper is to investigate a relevant case concerning a patient presenting with symptoms of acquired chronic intestinal pseudo-obstruction (CIPO). After one year of extensive diagnostic tests and unsuccessful treatment with prokinetics, the patient underwent a subtotal ileocolectomy. The histology of the intestinal specimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…4 Octreotide has been used with much success in CIP secondary to scleroderma. Gastrointestinal transit studies have demonstrated that, while octreotide has been proven to slow intestinal transit by inhibiting intermittent, low-amplitude contractions, it enhances short burst, high amplitude contractions.…”
Section: Discussionmentioning
confidence: 99%
“…4 Octreotide has been used with much success in CIP secondary to scleroderma. Gastrointestinal transit studies have demonstrated that, while octreotide has been proven to slow intestinal transit by inhibiting intermittent, low-amplitude contractions, it enhances short burst, high amplitude contractions.…”
Section: Discussionmentioning
confidence: 99%
“…56 Systemic sclerosis is suggested by skin involvement, Raynaud's phenomenon, microvascular abnormalities on capillaroscopy, and the presence of anti-topoisomerase I (SCL 70) antibodies. 57,58 TA B L E 2 Tests and investigations according to the suspected diagnosis in adult patients presenting with chronic intestinal pseudoobstruction (CIPO).…”
Section: Is E a S E S A Sso Ciated With Cip Omentioning
confidence: 99%
“…Systemic sclerosis is suggested by skin involvement, Raynaud's phenomenon, microvascular abnormalities on capillaroscopy, and the presence of anti‐topoisomerase I (SCL 70) antibodies 57,58 …”
Section: Diseases Associated With Cipomentioning
confidence: 99%
“…In fact, the extrinsic autonomic nervous system can be affected both centrally (for example, Parkinson's disease, vascular stroke, encephalitis, neoplasms and diseases affecting the encephalic autonomous centers) and peripherally (for example, diabetic neuropathy, or further neuropathies involving the enteric nervous system such as Hirschsprung Disease and Chagas Disease) [2,9]. This also includes paraneoplastic syndromes [10][11][12], immune-mediated [13,14] and collagen diseases, and viral infections. Furthermore, radiation enteritis, collagenosis, jejunal diverticulosis, and Ehlers-Danlos syndrome could cause neuronal and myogenic dysfunction [2].…”
Section: Introductionmentioning
confidence: 99%